2020
DOI: 10.3390/bios10040033
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensing of Serotonin by a Modified MnO2-Graphene Electrode

Abstract: The development of MnO2-graphene (MnO2-GR) composite by microwave irradiation method and its application as an electrode material for the selective determination of serotonin (SE), popularly known as “happy chemical”, is reported. Anchoring MnO2 nanoparticles on graphene, yielded MnO2-GR composite with a large surface area, improved electron transport, high conductivity and numerous channels for rapid diffusion of electrolyte ions. The composite was characterized by X-ray photoelectron spectroscopy (XPS), Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… Electrode LOD (µM) Sensitivity (µA µM −1 cm −2 ) Linear range/(µM) Ref. GR-FeTSPc/CFME 0.02 2.15 0.05–60 [38] rGO-Ag 2 Se 29.6 0.5 0.1–15 [39] Fe 3 O 4 –CNT–poly(BCG) 0.08 1.72 0.5–100.0 [40] PDMS@cZIF 0.03 2.45 1.0–60 [41] MnO 2 -GR 0.01 4.92 0.1–400 [42] SWCNT 32 0.919 0.1–100 [43] Carbon sphere 700 1.71 40–350 [44] Reduced graphene 32 5.26 1.0–100 [45] MWCNT/CHT 50 8.16 0.05–16 [46] MWCNT/Ni/Zn 118 5.38 0.006–62.8 [47] CNT/CHT/p-ABSA 8 4.26 0.1–522.6 [48] MnFe 2 O 4 /GCN 0.0031 19.377 0.025 – 909.12 This work GR-FeTSPc = graphene-iron-tetrasulfophthalocyanine, rGO-Ag 2 Se = reduced graphene oxide-silver selenide, Fe 3 O 4 –CNT–poly(BCG) = Fe 3 O 4 - multiwalled carbon nanotubes- ...…”
Section: Resultsmentioning
confidence: 99%
“… Electrode LOD (µM) Sensitivity (µA µM −1 cm −2 ) Linear range/(µM) Ref. GR-FeTSPc/CFME 0.02 2.15 0.05–60 [38] rGO-Ag 2 Se 29.6 0.5 0.1–15 [39] Fe 3 O 4 –CNT–poly(BCG) 0.08 1.72 0.5–100.0 [40] PDMS@cZIF 0.03 2.45 1.0–60 [41] MnO 2 -GR 0.01 4.92 0.1–400 [42] SWCNT 32 0.919 0.1–100 [43] Carbon sphere 700 1.71 40–350 [44] Reduced graphene 32 5.26 1.0–100 [45] MWCNT/CHT 50 8.16 0.05–16 [46] MWCNT/Ni/Zn 118 5.38 0.006–62.8 [47] CNT/CHT/p-ABSA 8 4.26 0.1–522.6 [48] MnFe 2 O 4 /GCN 0.0031 19.377 0.025 – 909.12 This work GR-FeTSPc = graphene-iron-tetrasulfophthalocyanine, rGO-Ag 2 Se = reduced graphene oxide-silver selenide, Fe 3 O 4 –CNT–poly(BCG) = Fe 3 O 4 - multiwalled carbon nanotubes- ...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding serotonin (SE) detection, MnO 2 nanoparticles have been anchored on graphene (GR) support, yielding MnO 2 -GR composite with a large surface area, improved electron transport, high conductivity and numerous channels for rapid diffusion of electrolyte ions [ 133 ]. Indeed, even if MnO 2 is one of the most promising transition MOX for electrochemical applications due to its non-toxicity, environmental compatibility and low cost [ 134 , 135 ], it is characterized by relatively poor electrical conductivity.…”
Section: An Overview On Mox Nanomaterials Used For Biosensing Detementioning
confidence: 99%
“…Recently, Lavanya et al [ 133 ] synthesized a MnO 2 -GR composite by the microwave irradiation method and fabricated an electrochemical sensor for detection of serotonin (SE) (see Figure 14 ). Microwave heating increases the rate of certain chemical reactions by several folds when compared to conventional heating.…”
Section: An Overview On Mox Nanomaterials Used For Biosensing Detementioning
confidence: 99%
“…A much improved LOD was obtained by the anchoring of MnO 2 nanoparticles on graphene by Nehru et al Here, the formed mesh-like structure possessed an increased surface area with a large number of channels that can facilitate the diffusion of analyte for a better activity. [142] SWV studies revealed a very low detection limit of 10 nM in a linear range of 0.1-800 µM. Some of the other conductive substrates of interest are conductive polymers, such as chitosan and carbon nanotube (CNT).…”
mentioning
confidence: 99%